More Stable Ties or Better Structure? An Examination of the Impact of Co-author Network on Team Knowledge Creation - Li, Mingze; Zhuang, Xiaoli; Liu, Wenxing; Zhang, Pengcheng (Frontiers in Psychology, 2017)
This study aims to explore the influence of co-author network on team knowledge creation. Integrating the two traditional perspectives of network relationship and network structure, we examine the direct and interactive effects of tie stability and structural holes on team knowledge creation. Tracking scientific articles published by 111 scholars in the research field of human resource management from the top 8 American universities, we analyze scholars’ scientific co-author networks. The result indicates that tie stability changes the teams’ information processing modes and, when graphed, results in an inverted U-shape relationship between tie stability and team knowledge creation. Moreover, structural holes in co-author network are proved to be harmful to team knowledge sharing and diffusion, thereby impeding team knowledge creation. Also, tie stability and structural hole interactively influence team knowledge creation. When the number of structural hole is low in the co-author network, the graphical representation of the relationship between tie stability and team knowledge creation tends to be a more distinct U-shape.